Wear Properties of Ash Minerals in Biomass - Lacey, Jeffrey A.; Aston, John E.; Thompson, Vicki S. (Frontiers in Energy Research, 2018)
Ash in biomass is believed to damage biorefinery equipment due to its abrasive properties. All biomass contains at least some ash, or inorganic content, as a result of normal physiological processes. The concentration of biogenic ash in biomass is largely species dependent; however it can also be affected by weather patterns, irrigation, soil type, and fertilizer applications. Ash concentrations in harvested biomass can also be elevated due to the incorporation of soil and dust during the harvest and collection processes. While ash concentration in biomass is important, so also is the mineral form of the ash. Certain mineral forms of ash can be much harder than the steels used to construct biorefinery equipment and cause excessive wear. In this perspective, the relative concentrations of ash elements, mineral forms of ash, and the hardness of these minerals are considered to identify ash components of concern to biorefinery operators. Strategies are suggested to remove ash from harvested biomass to reduce the risk of excessive wear on biomass processing equipment.